2016
DOI: 10.1111/nph.13996
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional oxidosqualene cyclases and cytochrome P450 involved in the biosynthesis of apple fruit triterpenic acids

Abstract: SummaryApple (Malus 9 domestica) accumulates bioactive ursane-, oleanane-, and lupane-type triterpenes in its fruit cuticle, but their biosynthetic pathway is still poorly understood.We used a homology-based approach to identify and functionally characterize two new oxidosqualene cyclases (MdOSC4 and MdOSC5) and one cytochrome P450 (CYP716A175). The gene expression patterns of these enzymes and of previously described oxidosqualene cyclases were further studied in 20 apple cultivars with contrasting triterpene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 54 publications
3
87
0
Order By: Relevance
“…Betula platyphylla), lupeol is oxidized at the C28 position by a cytochrome P450-dependent monooxygenase (CYP) to form BA (Figure 1) (Hamberger and Bak, 2013). Recently, a number of studies have reported enzymes of the CYP716A family to be responsible for this modification (Andre et al, 2016;Carelli et al, 2011;Fukushima et al, 2011;Moses et al, 2014). Based on the literature, we selected the Medicago truncatula CYP716A12 and CPR for expression in P. tricornutum.…”
Section: Introducing a Cyp716a12 Cytochrome P450 And A P450-nadph Redmentioning
confidence: 99%
“…Betula platyphylla), lupeol is oxidized at the C28 position by a cytochrome P450-dependent monooxygenase (CYP) to form BA (Figure 1) (Hamberger and Bak, 2013). Recently, a number of studies have reported enzymes of the CYP716A family to be responsible for this modification (Andre et al, 2016;Carelli et al, 2011;Fukushima et al, 2011;Moses et al, 2014). Based on the literature, we selected the Medicago truncatula CYP716A12 and CPR for expression in P. tricornutum.…”
Section: Introducing a Cyp716a12 Cytochrome P450 And A P450-nadph Redmentioning
confidence: 99%
“…Therefore, BfOSC2 is the first legume enzyme reported to produce mainly germanicol. Multifunctional OSCs that produce germanicol have been reported in Rhizophora styloza (mangrove; RsM1, produces germanicol : β‐amyrin : lupeol at a 63 : 33 : 4 ratio) (Basyuni et al ., ) and Malus domestica (apple; MdOSC4, produces germanicol : β‐amyrin : lupeol at an 82 : 14 : 4 ratio) (Andre et al ., ). Although BfOSC3 catalyzed the conversion of 2,3‐oxidosqualene to only α‐amyrin, we were puzzled by the inconsistency between the accumulation of α‐amyrin in B. forficata and the low productivity of BfOSC3 in yeast.…”
Section: Discussionmentioning
confidence: 97%
“…Plant/Enzyme name Accession no. et al, 2007) and Malus domestica (apple; MdOSC4, produces germanicol : b-amyrin : lupeol at an 82 : 14 : 4 ratio) (Andre et al, 2016). Although BfOSC3 catalyzed the conversion of 2,3oxidosqualene to only a-amyrin, we were puzzled by the inconsistency between the accumulation of a-amyrin in B. forficata and the low productivity of BfOSC3 in yeast.…”
Section: Enzymementioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, OSC enzymes can produce precursors for both non-sterol triterpenes, like lupeol, and sterol triterpenes, like cycloartenol [32]. To characterize the enzymatic product, OSC genes are often ectopically expressed in yeast [21, 30, 3335] or in plants via transient expression in Nicotiana benthamiana [36, 37]. …”
Section: Introductionmentioning
confidence: 99%